Effect of secondary phase on thermal behaviour and solid-state ion conduction in lithium doped N-ethyl-N-methylpyrrolidinium tetrafluoroborate organic ionic plastic crystal. Issue 47 (23rd November 2017) - Iranipour, N.; Gunzelmann, D. J.; Seeber, A. J.; Vongsvivut, J.; Hollenkamp, A. F.; Forsyth, M.; Howlett, P. C.
Abstract : Microstructural features significantly affecting lithium ion dynamics and conduction within the crystalline structure of pyrrolidinium based organic ionic plastic crystals. Abstract : An investigation of the equilibrium phase behaviour and the effect of lithium salt (lithium tetrafluoroborate) on the organic ionic plastic crystal (OIPC), N -ethyl- N -methylpyrrolidinium tetrafluoroborate [C2 mpyr][BF4 ] is described. In addition to the equilibrium phase transformations of the pure OIPC, new transitions were observed after the addition of the lithium salt (10 mol% and 20 mol% LiBF4 ), which significantly altered the ion conduction behaviour of the material. Attenuated total reflectance (ATR) FTIR spectroscopic results indicated that the molecular interactions between the lithium ion and the OIPC matrix were intensified with increasing lithium salt content. Variable temperature X-ray diffractograms revealed the existence of secondary and ternary phases within the microstructure of lithium ion containing OIPCs in the low temperature structures and during their transformations across the heating scans. Wide-line NMR data were consistent with the results obtained from XRD and DSC observations, indicating environments with varying dynamics for each of the ionic components (C2 mpyr +, BF4 − and Li + ) by increased lithium salt content.